(untitled) - Wise,Patricia S. (St. Louis, Mo., 1995)
Patricia Yoder-Wise blends the attributes which nurses exhibit in their practice, care and compassion, knowledge and skill, and logically demonstrates their application in leadership and management areas of nursing. Throughout the book, whether discussing the management of people or resources, Yoder-Wise emphasizes the need for nurses to continue to learn, to care, and maintain their passion for nursing.
Keywords: Nursing services,Leadership,Dịch vụ điều dưỡng,Lãnh đạo